Penguatan Karakter Kebangsaan dan Kompetensi Pedagogik Berorientasi Pada Keterampilan Abad 21 - Rahayu, Puji; Turmudi, Turmudi; Muharram, Agus; Kasmad, Mamad; Abdul Majid, Nuur Wachid (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
This research aims to reveal how the national character and pedagogic competence have oriented to 21st Century Skills for Students at Universitas Pendidikan Indonesia. This research used to qualitative that using case study approach. This research took place at UPI Campus Purwakarta. Informants at this time are: (1) leadership; (2) lecturers; and (3) students. Data analysis techniques using interactive models Miles and Huberman, namely: data collection, data condensation, display data, and concusion: drawing / verifying. The results of this research is the process of strengthening national character and mastery of pedagogic potential for PGSD UPI Students Purwakarta Campus is in accordance with the needs of 21st century skills. The learning process includes: (1) Project Based Learning; (2) Religious Tutorials; (3) Extracurricular Field Practices; and (4) Video Projects themed Local Wisdom. Through this method, they can help them to work in the world and be able to utilize pedagogic's teachers